Detrimental effect of anemia after mechanical thrombectomy on functional outcome in patients with ischemic stroke - Inui, Ryoma; Koge, Junpei; Tanaka, Kanta; Yoshimoto, Takeshi; Shiozawa, Masayuki; Abe, Soichiro; Ishiyama, Hiroyuki; Imamura, Hirotoshi; Nakahara, Jin; Kataoka, Hiroharu; Ihara, Masafumi; Toyoda, Kazunori; et al. (Frontiers in Neurology, 2023)
Background Anemia can occur due to an aspiration maneuver of blood with thrombi during mechanical thrombectomy (MT) for stroke. However, the association between postoperative anemia and stroke outcomes is unknown. Methods In a registry-based hospital cohort, consecutive patients with acute ischemic stroke who underwent MT were retrospectively recruited. Patients were divided into the following three groups according to their hemoglobin (Hb) concentrations within 24 h after MT; no anemia (Hb concentrations ≥13 g/dL for men and ≥ 12 g/dL for women), mild anemia (Hb concentrations of 11–13 g/dL and 10–12 g/dL, respectively), and moderate-to-severe anemia (Hb concentrations <11 g/dL and < 10 g/dL, respectively). A 3-month modified Rankin Scale score of 0–2 indicated a favorable outcome. Results Of 470 patients, 166 were classified into the no anemia group, 168 into the mild anemia group, and 136 into the moderate-to-severe anemia group. Patients in the moderate-to-severe anemia group were older and more commonly had congestive heart failure than those in the other groups. Patients in the moderate-to-severe anemia group also had more device passes than those in the other groups (p < 0.001). However, no difference was observed in the rate of final extended thrombolysis in cerebral infarction ≥2b reperfusion or intracranial hemorrhage among the groups. A favorable outcome was less frequently achieved in the moderate-to-severe anemia group than in the no anemia group (adjusted odds ratio, 0.46; 95% confidence interval, 0.26–0.81) independent of the baseline Hb concentration. A restricted cubic spline model with three knots showed that the adjusted odds ratio for a favorable outcome was lower in patients with lower Hb concentrations within 24 h after MT. Conclusion Moderate-to-severe anemia within 24 h after MT is independently associated with a reduced likelihood of a favorable outcome. Clinical trial registration https://www.clinicaltrials.gov, NCT02251665.